Rce1: mechanism and inhibition. (4th March 2018) - Hampton, Shahienaz E.; Dore, Timothy M.; Schmidt, Walter K.
Abstract: Ras converting enzyme 1 (Rce1) is an integral membrane endoprotease localized to the endoplasmic reticulum that mediates the cleavage of the carboxyl-terminal three amino acids from CaaX proteins, whose members play important roles in cell signaling processes. Examples include the Ras family of small GTPases, the γ-subunit of heterotrimeric GTPases, nuclear lamins, and protein kinases and phosphatases. CaaX proteins, especially Ras, have been implicated in cancer, and understanding the post-translational modifications of CaaX proteins would provide insight into their biological function and regulation. Many proteolytic mechanisms have been proposed for Rce1, but sequence alignment, mutational studies, topology, and recent crystallographic data point to a novel mechanism involving a glutamate-activated water and an oxyanion hole. Studies using in vivo and in vitro reporters of Rce1 activity have revealed that the enzyme cleaves only prenylated substrates and the identity of the a2 amino residue in the Ca1 a2 X sequence is most critical for recognition, preferring Ile, Leu, or Val. Substrate mimetics can be somewhat effective inhibitors of Rce1 in vitro . Small-molecule inhibitor discovery is currently limited by the lack of structural information on a eukaryotic enzyme, but a set of 8-hydroxyquinoline derivatives has demonstrated an ability to mislocalize all three mammalian Ras isoforms, giving optimism that potent, selective inhibitors might be developed. Much remains to be discovered regarding cleavage specificity, the impact of chemical inhibition, and the potential of Rce1 as a therapeutic target, not only for cancer, but also for other diseases.